Identifikasi Leptin pada Kesembuhan Luka Tikus yang Diberi Pakan Lemak Tinggi dan Aplikasi Zinc Topikal (LEPTIN IDENTIFICATION ON WOUND HEALING OF RAT GIVEN HIGH FAT DIET AND TOPICAL ZINC APPLICATION) - Anggraeni, Devita; Adji, Dhirgo; Sutrisno, Bambang (Jurnal Veteriner; Vol 13 No 4 (2012), 2013)
Leptin is a hormone produced by adipocytes and play an important role in wound healing. The objectiveof this research was to study the role of leptin in wound healing in mice experimentally given high fat dietsand its correlation to zinc. Thirty two male Sprague Dawley rats at three months of age were used in thisstudy. Rats were randomly allotted into four groups (A,B,C and D) of 8. Rats in group A and B were fednormal diet, while rats in group C and D were fed high fat diet. After two months of treatment, skin incisionsurgery was performed at the back side of the rat. Incision wound was closed with single interruptedsuture. The wound of rats in group A and C were treated with vaseline, while in the group B and D weretreated with zinc 10%. One day after surgery, blood sample were collected frpm four rats from each groupand analysed for leptin (Rat leptin ELISA Int, Genway Biotech Inc). Wounded skin from all animals werealso taken for histopathological examination (Haematoxylin and Eosin). Three days after the surgery, thesame analysis were done for the remaining rats. Leptin level was analyzed statistically using ANOVA forfactorial experiment, while histopathologic analysis was done descriptively. The results showed that theleptin level was significantly affected by time (P<0.05), as leptin level in blood at three days after surgerywas significantly lower than the level at one day after surgery. Meanwhile, histopathological examinationshowed that the percentage of epidermal closure in animals in group A,B,C,and D were 75%, 100%, 25%and 75%, respectivelly. Therefore, it was concluded that topical application of zinc might have significanteffect on the wound healing of the rats fed normal diets as well as these that given a high fat diet.
Keywords: leptin, zinc, high fat diet